Adjuvant chemotherapy is not a decisive factor in improving the overall survival of pulmonary sarcoma: A population-based study - Liang, Long; Liu, Zixuan; Wang, Changhui; Xie, Shuanshuan (Frontiers in Oncology, 2022)
Objective: This study aimed to investigate the impact of adjuvant chemotherapy on overall survival (OS) for pulmonary sarcomatoid carcinoma (PSC) and non-small cell lung cancer (NSCLC) cohorts and to identify its potential risk factors. Methods: A retrospective analysis study was performed by querying the Surveillance, Epidemiology, and End Results (SEER) database for patients diagnosed as PSC (n=460) and NSCLC (n=140,467) from 2004 to 2015. The demographics, tumor characteristics, treatment modes, and survival were included in the scope of statistical analysis. Confounding factors were controlled by propensity score matching (PSM) analysis. Kaplan-Meier survival curves were performed to compare the effects of adjuvant chemotherapy on OS of the patients in two cohorts (PSC vs NSCLC). A multivariable Cox regression model was constructed and Kaplan-Meier analysis on each variate was applied to predict risk factors associated with OS. Results: When adjuvant chemotherapy approach was applied in the treatment of patients with PSC or adjusted NSCLC respectively, the improved OS could be observed in NSCLC cohort (P=0.017). 1, 3, 5-year OS were 25.43%, 13.04% and 6.96% for the entire cohort in PSC compared to 41.96%, 17.39%, and 10.00% respectively for the new adjusted NSCLC cohort after PSM, which were statistically significant difference (P<0.001). Multivariable Cox regression analysis on OS covering prognostic factors such as primary site (P=0.036), first malignant indicator (P<0.001), age at diagnosis (P<0.001), marital status at diagnosis (P=0.039) and high school education (P=0.045). Additionally, patients with the following parameters had a worse impact on OS: a poorly differentiated pathology (Grade III/IV, P=0.023), older age (P<0.001), liver or lung metastasis (P=0.004, P=0.029), and the number of lymph nodes removed less than 4 (P<0.001). Conclusions: Adjuvant chemotherapy did not play a decisive role in improving the OS of PSC, while was associated with improved OS of NSCLC.